2014
DOI: 10.1111/bjh.12813
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic treatment for pregnancy complications: which path for the journey to precision medicine?

Abstract: SummaryHaemostatic and vascular biology mechanisms appear to play an important role in the pathogenesis of placenta-mediated pregnancy complications. Although low-dose aspirin (LDA) has a modest effect in preventing preeclampsia, antithrombotic interventions, LDA and low molecular weight heparin (LMWH) have not definitively proven their effectiveness in women with placenta-mediated pregnancy complications selected by previous pregnancy outcome alone. Given the heterogeneous aetiology of placenta-mediated pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 119 publications
(125 reference statements)
1
45
0
Order By: Relevance
“…LMWH probably has an early effect that may occur at cellular level, by decreasing trophoblast apoptosis and increasing the production of proteases involved in the trophoblast invasion of the maternal endometrium (23,24). In vitro studies have shown an effect of LMWH on angiogenesis in the placental villi and show an influence on the dysregulation of soluble vascular endothelial growth factor (25,26).…”
Section: <0001mentioning
confidence: 99%
“…LMWH probably has an early effect that may occur at cellular level, by decreasing trophoblast apoptosis and increasing the production of proteases involved in the trophoblast invasion of the maternal endometrium (23,24). In vitro studies have shown an effect of LMWH on angiogenesis in the placental villi and show an influence on the dysregulation of soluble vascular endothelial growth factor (25,26).…”
Section: <0001mentioning
confidence: 99%
“…This resonates with other trials that also showed no general benefit, including the ALIVE trial, where LDA and LMWH were used in women with recurrent pregnancy loss with preconceptional LDA use 1. Thus, EAGeR and a number of other trials show no benefit from antithrombotic interventions starting either before or following conception.…”
Section: Commentarymentioning
confidence: 51%
“…Although there is no consistent benefit from antithrombotic interventions for pregnancy complications in these trials, others have reported positive results 1. Therefore, it is important to make a better assessment of where the treatment is best employed, based on biological plausibility for effectiveness, before rejecting antithrombotics for prevention of pregnancy complications.…”
Section: Commentarymentioning
confidence: 99%
“…Those complications, such as preeclampsia, placental abruption, and birth of a small‐for‐gestational age neonate due to placental insufficiency and fetal death, remain leading causes of fetal‐maternal morbidity and mortality and are risk factors for maternal cardiovascular diseases . Effective preventive strategies and assessment of risk of recurrence do not currently exist . Controversy remains around the decision to perform thrombophilia testing or prescribe low‐molecular‐weight heparin.…”
Section: Women International Team: a Registry On Thrombophilia And Plmentioning
confidence: 99%
“…Participants of recurrence do not currently exist. [4][5][6][7][8] Controversy remains around the decision to perform thrombophilia testing or prescribe low-molecular-weight heparin. This is mostly based on the opinion of the consulting expert and sometimes the patient's preference.…”
Section: Introductionmentioning
confidence: 99%